2015
DOI: 10.1039/c4py01208a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dendritic polymers on nanomaterials

Abstract: Primary/secondary covalent/non-covalent interactions between dendritic polymers and nanomaterials can change the physicochemical properties, such as shape, of the obtained hybrid nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 135 publications
(142 reference statements)
0
28
0
Order By: Relevance
“…Several common solvents were tested for the Mizoroki-Heck cross-coupling reaction in the presence of MNP@PAMAM-Co to access the best optimal conditions ( Table 2, entries 13, [15][16][17][18][19][20]. This reaction proceeded in higher yields, more cleanly and faster when the reactions were conducted in a mixture of DMF and H 2 O in 1:1 ratio as solvent.…”
Section: Effect Of Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…Several common solvents were tested for the Mizoroki-Heck cross-coupling reaction in the presence of MNP@PAMAM-Co to access the best optimal conditions ( Table 2, entries 13, [15][16][17][18][19][20]. This reaction proceeded in higher yields, more cleanly and faster when the reactions were conducted in a mixture of DMF and H 2 O in 1:1 ratio as solvent.…”
Section: Effect Of Solventmentioning
confidence: 99%
“…So, to overcome these limitations, designing and applying a novel catalyst is required. [16,17] Attaching functional groups, such as hydroxyl, carboxyl and amine as terminal groups of the dendrimers can result in a considerable enhancement in binding capacity to a diversity of ions. For example, carbon nanotubes, despite having unique features, [7,12] are known to be hazardous to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that covalent functionalization of Gs with adequate organic units can improve G dispersability in different solvents minimizing restacking and rendering more persistent suspensions. Table compiles those reports in which covalent modification of Gs has been performed for the sake of better dispersability among other properties …”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Table 8c ompiles those reports in which covalentmodification of Gs has been performed for the sake of better dispersability among other properties. [245] Other uses of covalently modified Gs expand to very diverse fields going from adsorbents for CO 2 capture, [257] adsorption of dyes from water [258] or oil spill cleanup, [259] drug delivery, [260] development of non-volatile memory devices, [261] sensing applications including aptasensors, [262] electrical, [263] electrochemical or opticals ensors [263] or impedimetric biosensing, [264] among others. [265]…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…In order to overcome these barriers, it has been found that targeted, rational engineering to the dendrimer structure and their hybridization with other nanocarriers can be viable methods for controlling their biological interactions. (15) Some of these have included surface modifications, preparation of Janus, or two-faced dendrimers, alterations of the molecular architecture by integrating linear polymers, and hybridization with other NPs. This review will provide a comprehensive overview of these designs, focusing on the rational design and tweaking of dendritic nanomaterials to control their nano-bio interactions and tumor targeting behaviors.…”
Section: 0 Introductionmentioning
confidence: 99%